Current Therapeutic Approaches to Chronic Central Serous Chorioretinopathy - ŞAHİN, ÖZLEM (TURKISH OPHTHALMOLOGICAL SOC, 2019)
Central serous chorioretinopathy (CSCR) is the second most common maculopathy after diabetic maculopathy between the third and fifth decades of life. CSCR is characterized by serous neurosensory retinal detachment occasionally coexisting with retinal pigment epithelium (RPE) detachment. CSCR usually has good clinical prognosis, often resolving spontaneously within the first three months. However, some patients may have recurrent episodes and chronic disease. CSCR can cause permanent visual loss due to persistent neurosensory retinal detachment and RPE atrophy, especially in chronic cases. In recent years, verteporfin-photodynamic therapy applied with standard and low-dose/low-fluence protocols, anti-vascular endothelial growth factors, glucocorticoid antagonists, mineralocorticoid receptor antagonists, and subthreshold micropulse laser with varying parameters have been investigated as treatment options. In this review, we evaluated randomized and non-randomized case series conducted after 2000 that included at least 3 patients with chronic CSCR over 3 months in duration who were treated with current treatment options for chronic CSCR.
Keywords: Central serous chorioretinopathy; subthreshold micropulse laser; anti-vascular endothelial growth factor; verteporfin photodynamic therapy; FLUENCE PHOTODYNAMIC THERAPY; ENDOTHELIAL GROWTH-FACTOR; INDOCYANINE GREEN VIDEOANGIOGRAPHY; LASER MICROPULSE PHOTOCOAGULATION; INTRAVITREAL BEVACIZUMAB; FOLLOW-UP; CHOROIDAL THICKNESS; VERTEPORFIN; EFFICACY; TESTOSTERONE